Behind Closed Doors: Space, Experience, and Materiality in the Inner Areas of Brazilian Slave Houses. (3rd May 2016) - Souza, Marcos André Torres de
Abstract : This article focuses on the examination of some aspects of rural slavery in Brazil. Discussions will draw on the examination of data from two plantations from the eighteenth and nineteenth centuries. Through analysis of these case studies, this article exposes the mechanisms created in the landscape by plantation operators in order to exercise better control of captives' lives. This study also examines how enslaved individuals created reciprocal practices and domains of knowledge within living areas that allowed them to produce and reproduce practices on their own. The conclusion of this text stresses the significance of the enslaved individuals' living places for their cultural and social survival.